Investigation of magnetic field inter-harmonics and sideband vibration in FSCW IPMSM drive with SPWM technique - Wenyi, Liang; Luk, Patrick Chi-Kwong; Fei, Wei-Zhong (IEEE, 2017)
The high-frequency sideband current harmonics are the inherent concomitants of applying sinusoidal pulse width modulation (SPWM) in permanent magnet synchronous machine drives. Abundant spatial interharmonic magnetic field components in fractional-slot concentrated-winding (FSCW) interior permanent magnet synchronous machine (IPMSM) render it very susceptible to electromagnetic radial vibration (ERV). In this paper, a universal analytical interharmonic model of magnetic field in FSCWIPMSMs is proposed, and further it is employed to develop the sideband radial force density model of SPWM. Both comprehensive finite element analysis (FEA) simulations and experimental tests are carried out to underpin the validity of the analytical models. The close agreements between the analytical, FEA, and experimental results have revealed that the proposed analytical approaches can deliver accurate sideband current and vibration predictions with minimum computational efforts and suffice for fast preliminary assessments. In addition, the validated analytical models can offer detailed and insightful revelations of various factors that affect the corresponding sideband vibration components.
Keywords: Concentrated-winding; electromagnetic radial force density; electromagnetic radial vibration; fractional-slot; magnetic flux density; permanent magnet synchronous machine drive; sideband harmonic; sinusoidal pulse width modulation